2004
DOI: 10.1007/s00027-004-0705-x
|View full text |Cite
|
Sign up to set email alerts
|

Essential characteristics of natural dissolved organic matter affecting the sorption of hydrophobic organic contaminants

Abstract: Association of benzo[a]pyrene (BaP), pyrene, 3,3¢,4,4¢-tetrachlorobiphenyl (TCB) and 2,2¢,4,4¢-tetrabromo diphenyl ether (TBDE) with natural dissolved organic matter (DOM) was studied. The DOM samples were previously collected from natural waters at five Nordic sites during fall 1999 and spring 2000, isolated by the reverse osmosis method, and thoroughly characterized. The purpose was to determine the essential characteristics that predict the sorption capacity of DOM for hydrophobic contaminants. DOM isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 38 publications
5
46
1
Order By: Relevance
“…The properties of DOM, such as molecular size, weight [24,25], and aromaticity of DOC, affect the sorption of anthropogenic hydrophobic organic chemicals [14], as observed in the current study. Our results showed that all three model compounds sorbed more to HAs than to FAs.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The properties of DOM, such as molecular size, weight [24,25], and aromaticity of DOC, affect the sorption of anthropogenic hydrophobic organic chemicals [14], as observed in the current study. Our results showed that all three model compounds sorbed more to HAs than to FAs.…”
Section: Discussionmentioning
confidence: 88%
“…In the aquatic environment, hydrophobic compounds tend to associate with dissolved organic matter (DOM) and particulate organic matter. The partition coefficient of BDE-47 in artificial fresh water dissolved organic carbon (DOC) systems (DOC concentration of 15 mg/L) was from 4.57 to 4.90 (log K DOC ) [14].The source of DOM greatly affects the sorption of BaP [14,15]. In addition, increasing water hardness has been shown to slightly decrease sorption of organic compounds to DOM [14].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…When present in lakes, TOC affects transparency and thereby the temperature and thermal stratification of lake (Keskitalo and Eloranta 1999;Findlay and Sinsabaugh 2003) and the structure of aquatic food webs (Jansson et al 2000;Kankaala et al 2010). It also has impacts on the acid-base chemistry of surface waters (Buffam et al 2008), C budgets of catchments (Kindler et al 2011;Schelker et al 2012), greenhouse gas fluxes , and the mobility, toxicity and bioavailability of organic pollutants and trace metals such as mercury (Porvari et al 2003;Akkanen et al 2004;Ravichandran 2004;Bergknut et al 2011).…”
Section: Introductionmentioning
confidence: 99%